Private dysferlin exon skipping mutation (c.5492G>A) with a founder effect reveals further alternative splicing involving exons 49-51 - Santos, Rosário (2011)
The allelic muscle disorders known as limb-girdle muscular dystrophy type 2B (LGMD2B), Miyoshi myopathy and distal anterior compartment myopathy result from defects in dysferlin—a sarcolemma-associated protein involved in membrane repair. Mutation screening in the dysferlin gene (DYSF) enabled the identification of seven Portuguese patients presenting the variant c.5492G4A, which was observed to promote skipping of exon 49 (p.Gly1802ValfsX17). Several residually expressed products of alternative splicing also involving exons 50 and 51 were detected in the leukocytes and muscle of both patients and normal controls. Quantitative transcript analysis confirmed these results and revealed that D49/D50 transcripts were predominant in blood. Although the patients were apparently unrelated, the c.5492G4A mutation was found in linkage disequilibrium with a particularly rare haplotype in the population, corroborating the hypothesis of a common origin. Despite the presence of the same mutation on the same haplotype background, onset of the disease was heterogeneous, with either proximal or distal muscle involvement.